Study on Dual-Concentric-Core Dispersion Compensating Photonic Crystal Fiber - Habib, Md. Selim; Habib, Md. Samiul; Razzak, S.M.A (International Journal of Engineering and Technology, 2012)
The dual-concentric-core photonic crystal fiber composed of pure silica and air is proposed in this paper. Around 1.55 ?m, it exhibits a negative chromatic dispersion as high as –20000 ps/(km.nm). The finite element method with perfectly matched absorbing layers boundary condition is used to investigate the guiding properties. The explanations to propagation states of the fundamental mode and the second mode are given elaborately